Pengaruh Kompetensi Aparat Pengelola Dana Desa, Komitmen Organisasi Pemerintah Desa Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana - Sundanah; Yuwita Ariessa Pravasanti; Sri Laksmi Pardanawati (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This study aims to determine the Effect of Competence of Village Fund Management Apparatus, Village Government Organizational Commitment, and Community Participation on Village Fund Management Accountability. The research method used is a quantitative method. Sources of data used are primary data obtained from distributing questionnaires. The population in this study were 19 villages in Juwiring District, Klaten Regency with 100 respondents. The sampling technique used purposive sample. The data in this study were processed using multiple linear regression tests with the help of the SPSS version 23 program. Based on the results of the study, it can be concluded that the village government organizational commitment and community participation have a positive influence on Village Fund Management Accountability in Juwiring District, Klaten Regency, while the Competence of the Management Apparatus Village Funds have no effect on Accountability of Village Fund Management in Juwiring District, Klaten Regency.